Efficacy and safety of baricitinib and tocilizumab in hospitalized patients with COVID-19: A comparison using systematic review and meta-analysis - Cherian, Jerin Jose; Eerike, Madhavi; Bagepally, Bhavani Shankara; Das, Saibal; Panda, Samiran (Frontiers in Pharmacology, 2022)
Objective: This review was performed to compare the efficacy and safety among hospitalized patients with COVID-19 who received baricitinib and those who received tocilizumab independently with placebo or the standard of care (SOC). Methods: Relevant databases were searched for randomized controlled trials which evaluated the effect of baricitinib or tocilizumab as compared to placebo or the SOC in hospitalized patients with COVID-19. The primary endpoint was the comparison of the 28-day mortality. Risk ratios (RR) and mean differences were compared and pooled for dichotomous and continuous variables, respectively. A two-staged exploratory network meta-analysis using a multivariate meta-analysis was also performed. All analyses were performed in Stata version 16.0. The GRADE approach was used to assess the quality of the generated evidence (PROSPERO ID: CRD42022323363). Results: Treatment with baricitinib [RR, 0.69 (95% CI, 0.50 to 0.94), p=0.02, i2=64.86%] but not with tocilizumab [RR, 0.87 (95% CI, 0.71 to 1.07), p=0.19, i2=24.41%] led to a significant improvement in the 28-day mortality as compared to that with the SOC. Treatment with baricitinib or tocilizumab, both independently led to a significant reduction in the duration of hospitalization [baricitinib: mean difference, -1.13 days (95% CI, -1.51 to -0.76), p<0.001, i2=0.00%; tocilizumab: mean difference, -2.80 days (95% CI, -4.17 to -1.43), p<0.001, i2=55.47%] and a significant improvement in the proportion of patients recovering clinically by day 28 [baricitinib: RR, 1.24 (95% CI, 1.03-1.48), p=0.02, i2=27.20%; tocilizumab: RR, 1.41 (95% CI, 1.12-1.78), p<0.001, i2=34.59%] as compared to those with the SOC. From the safety point of view, both these drugs showed similar results. There were fewer patients who experienced any serious adverse event following treatment with barictinib and tocilizumab as compared to those following treatment with the SOC [baricitinib: RR, 0.76 (95% CI, 0.62 to 0.92), p=0.01, i2=12.63%; tocilizumab: RR, 0.85 (95% CI, 0.72 to 1.01), p=0.07, i2=0.00%]. Conclusion: As baricitinib and tocilizumab are recommended interchangeably by various guidelines for the management of COVID-19, considering the better 28-day mortality data and other comparable efficacy and safety outcomes, baricitinib may be favored over tocilizumab considering its ease of administration, shorter half-life, and lower cost of treatment.